Human Rights Education in Colombia: State of the Art of Research in Formal Education: Educación en derechos humanos en Colombia: estado del arte de las investigaciones en la educación formal (Papeles, 2022)
Introduction: This article collects the historical development of Human Rights Education (HRE) in Colombia. Methodology: The research is based on national and international studies and research that have taken it as an object of analysis. Results and Discussion: According to what was found, there are four major research trends on which academic production has focused: historical development of human rights and HRE; methodological proposals for HRE; teaching of human rights and some necessary relationships; and presence of human rights in the school. Conclusions: The contributions that have been made in terms of HRE, the tensions that exist in its exercise at school and in general in formal education and the pending issues to be addressed in the field are evident.
Keywords: Human rights education; human rights; school; teaching; curriculum; citizen education